2015
DOI: 10.4314/tjpr.v14i10.12
|View full text |Cite
|
Sign up to set email alerts
|

Ebracteolatain A and Ebracteolatain B Induce Apoptosis of Human Hepatoma Cell Line (HepG2)

Abstract: Purpose: To evaluate the effects of ebracteolatain A (EA) and ebracteolatain B (EB) from and up-regulated the expression levels of proapoptotic proteins (Smac, Bax, in mitochondria-mediated apoptotic pathway. Conclusion: EA and EB inhibit the proliferation of HepG2 cells, the probable mechanisms being associated with mitochondria-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the present study, the cytotoxic activity of PA against BGC823 cells was related to apoptosis, and the mechanisms of action were linked to activation of death receptor-and mitochondriamediated apoptotic pathways. The MTT assay is a standard procedure for assessing the viability of cancer cells [20], while flow cytometry is used for investigating apoptosis in cancer cells [21]. The results obtained from these assay methods indicated that PA exerted good apoptosis-related cytotoxic activity against BGC823 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the cytotoxic activity of PA against BGC823 cells was related to apoptosis, and the mechanisms of action were linked to activation of death receptor-and mitochondriamediated apoptotic pathways. The MTT assay is a standard procedure for assessing the viability of cancer cells [20], while flow cytometry is used for investigating apoptosis in cancer cells [21]. The results obtained from these assay methods indicated that PA exerted good apoptosis-related cytotoxic activity against BGC823 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The plates were subjected to incubation for 4 h at 37°C, at the end of which the RPMI-1640 medium was removed, and the cells were incubated with 200 μL DMSO in the dark for 30 min to dissolve the resultant blue-violet formazan crystals. The absorbance values of the formazan solutions were read in a Bio Rad microplate reader (Model 680, USA) at 570 nm against a blank of DMSO [14,15].…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…ex Boiss., Euphorbia hirta L., Euphorbia ingens E. Mey. ex Boiss., Euphorbia lathyrism L., Excoecaria agallocha L., Euphorbia helioscopia L., and Ricinus communis L. extracts [ 67 , 68 , 70 , 94 , 95 , 115 , 211 , 215 ], and the pure compounds Euphorbia Factor L2, Ebracteolatain A, and Ebracteolatain B [ 147 , 232 ], activate the intrinsic pathway at some point. DNA damage promotes the liberation of cytochrome C by mitochondria.…”
Section: Potential Anticancer Mechanism Of Action Of Euphorbiaceae Ex...mentioning
confidence: 99%
“…p53 is a tumor-suppressive protein with the ability to induce cell death, including through apoptotic mechanisms and other transcription-dependent mechanisms or independent mechanisms [ 235 ]. Zhou et al [ 232 ] also found that the activity of the pure compounds Ebracteolatain A and Ebracteolatain B increased p53 levels and decreased survivin levels. Survivin is a survival protein that inhibits caspases and blocks cell death [ 236 ].…”
Section: Potential Anticancer Mechanism Of Action Of Euphorbiaceae Ex...mentioning
confidence: 99%
See 1 more Smart Citation